(untitled) (Revista de Ciências Agroveterinárias, 2022)
The aim of the current study is to evaluate deforestation in mangaba tree (Hancornia speciosa Gomes) growing areas and environmental valuation in fairs held in Sergipe State, in order to suggest environmental service payment mechanisms to help conserving natural mangaba tree-growing areas in the state. Land use and cover, as well as deforestation, were measured based on MapBiomas data. Information about annual mangaba production was extracted from data provided by IBGE on Vegetable Extraction and Silviculture Production. The environmental valuation by mangaba consumers at fairs was measured through questionnaire application. Natural mangaba tree-growing areas in Sergipe State have shown low rates of forest cover and natural non-forest sites in the last 34 years. However, these areas are mainly used for agricultural purposes, a fact that compromises mangaba production. Sergipe State has shown considerable reduction in mangaba production rates from 1995 to 2016; however, such a production presented remarkable recovery in the last three years. Contingent valuation has shown that potential stakeholders are willing to financially contribute to the conservation of both mangaba trees and the Atlantic Forest.